Berlin Art Scene : A Double Mentality. (Tokyo : Sezon Museum of Art, 1991)
Florschuetz, Thomas ; Görss, Rainer ; Gries, Gero ; Jokl, Ivonne ; Killisch, Klaus ; Lewandowsky, Via ; Munk, Bettina ; Rheinsberg, Raffael ; Schwarz, Oliver ; Stück, Norbert ; Tolaas, Sissel ; Zey, Georg
Berlin Art Scene : A Double Mentality, Sezon Museum of Art, Tokyo, 14 November - 24 Dezember 1991 ; Amagasaki, Tsukashin Hall, 16 February - 29 March 1992 ; Iwaki, Iwaki City Art Museum, Iwaki, 4 April - 10 May 1992 ; etc.
English-Japanese
kunstcatalogus
Keywords: Berlijn